Embates ideológicos em torno da palavra “diálogo” durante a implementação da reorganização escolar de 2015 - Galelli, Cinthia Yuri [UNESP]; Bedê, Luiza [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2017)
According to Bakhtin’s perspective on discourse, words possess two concomitant ways of existence in language. One of them is that which remains stable and reproducible; it is called meaning. The other one, the theme, is unitary and unreproducible, which allows clashes of different social voices to exist, demonstrating the ideologies which operate over them. With the concepts developed by the Bakhtin Circle, we will analyze the discourses produced during the occupations made by high- school students in the state public schools of São Paulo, in the second semester of 2015. These occupations were motivated in response to the project of school reorganization proposed by the state government. In the present work, we will contrast two discourses: the one from those who were against the school reorganization, that is, the high-school students, and the one from the government, the project proponent. These discourses generated ideological conflicts around the word “dialogue”; our study is built on these tensions. To the analysis of the students’ discourse, we will use the documentary “Acabou a paz: isto aqui vai virar o Chile”, by Carlos Pronzato, as corpus. The analysis of the government discourse corresponds, in this article, to the utterances produced by Governor Geraldo Alckmin, by Herman Voorwald, former Secretary of Education of São Paulo, and by Fernando Padula, former chief of staff of the Secretariat of Education. The utterances were taken from different interviews. The analysis, based on the bakhtinian theoretical framework, has developed different meanings related to the different social voices that the word “dialogue” assumed during the studied period.
Ideological conflicts on the word “dialogue” during the implementation of the school reorganization of 2015
Keywords: Bakhtin circle; Dialogue; Ideology; School reorganization; Social voices